The Hunger Games Faculty Guide - Kansas State University, K-State First (Kansas State University. K-State First., 2010)
This guide provides information and themes on Kansas State University's inaugural common book "The Hunger Games" by Suzanne Collins. The guide also provides an introduction to the K-State Book Network (KSBN) and a rational on why we should read a common book. Themes included leadership, social issues, media, sciences, and survival skills.
Keywords: Hunger Games, The; Guide; Common reading program; First-year experience program; Faculty development; Brochures